Exploration and Research on Ideological and Political Education in Higher Vocational Education Curriculum: Taking the Course of "Online Store Operation and Management" as an Example - Zhang, Lili (Journal of Theory and Practice of Contemporary Education, 2023)
Ideological and political literacy affect students' future development. Only by strengthening ideological and political education can students' comprehensive literacy be improved, and each course is a crucial ideological and political education battlefield, playing an important role in ideological and political education. In the process of rapid development of information technology and e-commerce, the e-commerce major has received much attention, and "Online Store Operation and Management" plays an important role in ideological and political education. Teachers should integrate ideological education elements into the curriculum teaching based on the characteristics and teaching content of the course, and strengthen the guarantee of teachers and curriculum evaluation, laying the foundation for the implementation of ideological and political education in the curriculum.